2016
DOI: 10.1097/hcr.0000000000000178
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life Improves Similarly in Patients With and Without Type 2 Diabetes After Cardiac Rehabilitation

Abstract: These results suggest that D and N-D patients do not differ in their HRQoL at the start or end of CR, and that the 2 groups show similar improvements from attending the program. Larger sample studies are needed to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Therefore, education is an essential part of diabetes care, helping patients navigate through these processes. Cardiac rehabilitation (CR), a comprehensive secondary prevention program, is increasingly recognized as an integral component of the continuum of care for cardiovascular patients3,4 and studies have shown its positive effects on patients with diabetes 5–8. Patient education is a core component and a quality indicator of CR9,10; therefore, this secondary prevention strategy can not only provide lifestyle modification and risk factor management, but also educate people with diabetes.…”
mentioning
confidence: 99%
“…Therefore, education is an essential part of diabetes care, helping patients navigate through these processes. Cardiac rehabilitation (CR), a comprehensive secondary prevention program, is increasingly recognized as an integral component of the continuum of care for cardiovascular patients3,4 and studies have shown its positive effects on patients with diabetes 5–8. Patient education is a core component and a quality indicator of CR9,10; therefore, this secondary prevention strategy can not only provide lifestyle modification and risk factor management, but also educate people with diabetes.…”
mentioning
confidence: 99%